A comparison of estimated drug costs of potentially inappropriate medications between older patients receiving nurse home visit services and patients receiving pharmacist home visit services: a cross-sectional and propensity score analysis - Hamano, Jun (BMC Health Serv Res, 2015)
BACKGROUND: There have been no multicenter studies that estimated the relations of either nurse or pharmacist home visit program to drug costs of potentially inappropriate medications (PIMs). This study aimed to establish whether patients who used nurse or pharmacist home visit programs (nurse or pharmacist program) had lower drug costs of PIMs than those who did not use nurse or pharmacist programs for older patients living at home. METHODS: This cross-sectional study was conducted in home care settings in Japan, involving 430 patients aged 65 or older, of whom 276 were female. All received regular home visits from five clinics between May and December 2013. After the PIMs were identified with the Screening Tool of Older Persons' potentially inappropriate Prescriptions (STOPP) criteria, we estimated the drug costs based on actual pharmaceutical prices and measured against who using nurse or pharmacist programs after a propensity score weighted adjustment. RESULTS: Patients who used nurse programs had lower drug cost of PIMs than those who did not use, but it was not significantly different (5.9 ± 13.1 vs 7.1 ± 13.9 USD per month, P = 0.199). The cost of PIMs for patients who used pharmacist programs also had no difference. (7.2 ± 14.5 vs 5.5 ± 11.5 USD per month, P = 0.06). In the patient groups who used nurse programs, patients who also used pharmacist programs had significantly higher costs of PIMs than those who used only nurse programs (5.5 ± 13.9 vs 2.5 ± 6.0 USD per month, P = 0.006). In patients group who did not use pharmacist programs, patients who only used nurse programs had significantly lower costs of PIMs than those who did not use nurse programs (3.6 ± 7.7 vs 5.8 ± 12.7 USD per month, P = 0.022). CONCLUSIONS: Patients who used nurse program have a trend towards lower drug costs of PIMs than those who used nurse and pharmacist program or pharmacist program alone. Although this study tried to adjust the potential confounders as possible as we could by using propensity score analysis, further studies are needed to confirm our results.